The Impact of Environmentally Oriented Project-Based Learning on Students’ Environmental and Science Literacy - Andi Zulfikar Syaiful; Ridwan Ridwan; Djusdil Akrim; Imaduddin Murdifin; Irfan Tawakkal (Jurnal Pendidikan MIPA, 2026)
Used cooking oil is a type of liquid waste that can pollute land and water. Processing used cooking oil requires knowledge and the application of scientific principles because it contains various chemical compounds formed during frying. Reusing it or processing it into other products requires an understanding of its chemical properties and the reactions that occur; therefore, education on handling used cooking oil waste requires appropriate learning methods. One appropriate learning method to implement is Project-Based Learning (PjBL). This research aimed to analyze the impact of implementing PjBL for Soap Production from vegetable oil waste on improving students' environmental and science literacy. The study was quasi-experimental and conducted using a pretest-posttest control group design. The sample included students from Muhammadiyah Lajoa Secondary School in Soppeng Regency, South Sulawesi, Indonesia. The total sample size was 76 students, divided into 38 in the comparison group and 38 in the experimental group. In line with the research findings, teaching the basics of ecology and natural science using PjBL yielded superior outcomes compared to traditional methods. The Mann-Whitney test revealed a significant difference in the normalized gain (N-gain) scores for knowledge of natural science and the environment (p<0.001) between the control and PjBL groups. Students using the PjBL method produced solid soap by following the correct steps of the soap-making process. A Wilcoxon signed-rank test showed a significant increase (p<0.001) after two stages of the soap-making cycle. Thus, the implementation of PjBL has a significant impact on improving students' literacy. Keywords: project-based learning, environmental literacy, science literacy, used cooking oil, soap.